The inclusion of blind children in physical education classes: Difficulties and opportunities - DOI: 10.4025/actascihumansoc.v27i2.204 - Alves, Maria Luíza Tanure (2007)
Inclusion has the purpose of building a society capable of promoting the socialization and social participation of all citizens. Blindness brings a relevant loss of information for the visually impaired. This loss, reduces the opportunities that blind people may have to interact with the environment and the people around them. Our study consists of a bibliographic review on inclusion from 1990 to 2004. The authors’ main ideas from the most important research work in the area were collected, analyzed and turned into a useful tool for physical education teachers that deal with this special group. physical education classes may provide the inclusion of the visually impaired throughout flexible activities. Nevertheless, teachers insist on having negative attitudes which are consequences of their lack updating in training. 7.08.00.00-6 Educação